2022
DOI: 10.1002/ccr3.5827
|View full text |Cite
|
Sign up to set email alerts
|

Dohsa‐hou for unexplained regression in Down syndrome in a 19‐year‐old man: A case report

Abstract: In the last decade, regression-like symptoms in adolescents and young adults with Down syndrome have become a major issue. Previous studies illustrated the symptoms as deterioration in daily living skills, social relationships, mental health status, and motor functioning, which included various symptoms, such as anxiety, depression, loss of skills, withdrawal, motor slowness, insomnia, mutism, obsessive-compulsive behavior, and catatonia. [1][2][3][4][5] This syndrome, observed in young adults with Down syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…11 Fujino 12 found Dousa-hou an effective approach to maladaptation and internalization problems in young adults with Down syndrome. In a later study, Fujino and Moritsugu 13 reported the advantages of engaging in physical movement for adolescents with Down syndrome and severe intellectual disabilities. Norouzi et al 14 suggested that Dousa-hou led to bimanual coordination in children with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…11 Fujino 12 found Dousa-hou an effective approach to maladaptation and internalization problems in young adults with Down syndrome. In a later study, Fujino and Moritsugu 13 reported the advantages of engaging in physical movement for adolescents with Down syndrome and severe intellectual disabilities. Norouzi et al 14 suggested that Dousa-hou led to bimanual coordination in children with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%